Study protocol for a randomised controlled trial of brief, habit-based, lifestyle advice for cancer survivors: exploring behavioural outcomes for the Advancing Survivorship Cancer Outcomes Trial (ASCOT). Issue 11 (23rd November 2016) - Beeken, Rebecca J; Croker, Helen; Heinrich, Maggie; Smith, Lee; Williams, Kate; Hackshaw, Allan; Hines, John; Machesney, Michael; Krishnaswamy, Madhavan; Cavanagh, Sharon; Roylance, Rebecca; Hill, Alison; et al.
Abstract : Introduction: Positive health behaviours such as regular physical activity and a healthy diet have significant effects on cancer outcomes. There is a need for simple but effective behaviour change interventions with the potential to be implemented within the cancer care pathway. Habit-based advice encourages repetition of a behaviour in a consistent context so that the behaviour becomes increasingly automatic in response to a specific contextual cue. This approach therefore encourages long-term behaviour change and can be delivered through printed materials. 'Healthy Habits for Life' is a brief intervention based on habit theory, and incorporating printed materials plus a personally tailored discussion, that has been designed specifically for patients with a diagnosis of cancer. The aim of this trial was to test the effect of 'Healthy Habits for Life' on a composite health behaviour risk index (CHBRI) over 3 months in patients with a diagnosis of breast, colorectal or prostate cancer. Method and analysis: A 2-arm, individually randomised controlled trial in patients with breast, colorectal and prostate cancer. Patients will be recruited over 18 months from 7 National Health Service Trusts in London and Essex. Following baseline assessments and allocation to intervention or usual care, patients are followed up at 3 and 6 months. The primary outcome will be change in CHBRI at 3 months. Maintenance of any changes over 6 months, and changes in individual health behaviours (including dietary intake, physical activity, alcohol consumption and smoking status) will also be explored. Ethics and dissemination: Ethical approval was obtained through the National Research Ethics Service Committee South Central—Oxford B via the Integrated Research Application System (reference number 14/SC/1369). Results of this study will be disseminated through peer-reviewed publications and scientific presentations. Trial registration number: 17421871.